A study of measles in adults at Charlotte Maxeke Johannesburg Academic Hospital - Diana, Nina Elisabeth (My University, 2015)
childhood illness, there are an increasing number of cases occurring in adults. Objectives The objectives were to describe the clinical characteristics and outcomes of adult patients admitted with measles and to compare these parameters in HIV-seropositive and HIV-seronegative cases. Methods A retrospective record review of adult patients confirmed to have measles admitted to the Infectious Disease Unit at Charlotte Maxeke Johannesburg Academic Hospital from 1 October 2009 to 31 March 2010 was conducted. Data collected included demographic, clinical, laboratory, radiographic parameters, and outcomes. HIV-positive and HIV-negative patients were compared with respect to the above parameters. Results Overall 33 patients were included in this analysis, of whom 18 (54.5%) were female, all were of black African descent and their mean age was 27.8 ± 5.8 years. Median duration of symptoms was 4 days (range 1 – 7 days). All patients had a morbilliform rash and conjunctivitis on presentation. Twelve patients (36.4%) had a clinical course complicated by pneumonia. Six of these patients (18.2% of the total group) were admitted to ICU/High care; three of whom developed respiratory failure requiring mechanical ventilation, and acute kidney injury. Other complications included purulent conjunctivitis (3%), pancreatitis (3%) and encephalitis (3%). Median length of hospital stay was 3 days (range 1 – 31 days). Three patients (9.1%) demised. A total of 24 patients were tested for HIV infection and 18 tested seropositive. More female patients tested positive for HIV infection. HIV-infected patients had a longer length of hospital stay (p = 0.03). Conclusion Measles continues to cause morbidity and mortality in adult patients. More severe consequences occur in HIV-positive patients.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine Johannesburg 2015